Can't you sleep, Little Bear? - Waddell, Martin; Firth, Barbara (Cambridge, Mass. : Candlewick Press, 1994)
When bedtime comes Little Bear is afraid of the dark, until Big Bear brings him lights and love.
Booklist
Publisher's Weekly
School Library Journal
K-3.
K-3
Keywords: Bears -- Fiction; Bedtime -- Fiction; Fear of the dark -- Fiction; Bears -- Fiction; Bedtime -- Fiction; Fear of the dark -- Fiction